IMPLEMENTASI KOMUNIKASI, INFORMASI DAN EDUKASI KELUARGA BERENCANA - Irwanto (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2021)
This research aims to determine the effect of Communication, Resources, Disposition and Bureaucratic Structure in the implementation of Communication, Information and Education of Family Planning, both simultaneously and partially on the participation of fertile age couples (PUS) KB Long-Term Contraception Method (MKJP) in the City. Pekanbaru. This research type is a quantitative approach with survey methods and quantitative / statistical data analysis. Primary data collection through questionnaires to 35 respondents to the City Family Planning Extension Officer. Pekanbaru and secondary data through other data relating to the problem under study. The analysis method uses descriptive statistical analysis and inferential statistical analysis with the help of the SPSS application. The results showed that simultaneously the variables of Communication, Resources, Disposition and Bureaucratic Structure had a significant effect on the Participation of Fertile Age Couples in the Long-Term Contraception Method with a calculated f value (6.129)> f table (2.69) and the contribution of the coefficient of determination (R2) of 75.0%. With the remaining 25.0% influenced by other variables not examined in this research.